Familial TGCT: polygenic aetiology advanced. Issue 11 (November 2018) - Greene, Mark; Pfeiffer, Ruth
A polygenic risk score (PRS) analysis reported that familial testicular germ cell tumours (TGCTs) were significantly enriched for TGCT risk alleles and that ≥84% were attributable to polygenic enrichment, supporting the polygenic aetiological basis of familial TGCT. Clinical application will first require improved TGCT screening and early detection tools.